The current status, relevance and impact of the sense of gain and social participation among Chinese youth: A study based on the CSS2021 database. - He Yang; Changan Li; Liujun Ye (PLoS ONE)
Youth symbolize the future and promise of the country. The contributions of youth are integral to the comprehensive development, the social participation of youth is crucial for their holistic development and the betterment of society. As the people's sense of gain has evolved into a fundamental aspect of high-quality development in the new era of China, investigating the influence mechanism of the youth's sense of gain on social participation holds significant historical and practical relevance. This study utilizes the CSS2021 database to conduct empirical analysis, centered on three pivotal dimensions, the youth's sense of political gain, economic gain, and people's livelihood gain, this study explores their influence on social participation across affairs, rights protection, and people's livelihood, and the study further delves into the specific impact mechanisms through which the youth's sense of gain influences social participation. The results distinctly demonstrate that the sense of gain within the youth group significantly influences the enthusiasm for social participation. The study reveals specific associations: the sense of economic gain negatively correlates with social participation in affairs and rights protection, while the sense of people's livelihood gain demonstrates a positive correlation with rights protection. Additionally, a noteworthy positive correlation exists between political gain and social participation. Consequently, there is a suggestion that the government could better understand the core demands of young individuals, thereby fostering increased enthusiasm for their social participation. Leveraging the active engagement of young people could significantly contribute to enhancing the government's governance effectiveness.